Coma Aberration of a Nonlinear Aspherical Micro-Lens Created by Kerr medium - Xuan Kien, Bui; Quang, Pham Thanh; Tuan, Tran Quoc (VNU Journal of Science: Mathematics - Physics; Vol 42 No 2DO - 10.25073/2588-1124/vnumap.5111, 2026)
A nonlinear aspherical micro-lens (NAML) can be dynamically formed inside a Kerr medium under Gaussian beam (GB) illumination, providing an intensity-dependent optical surface that enables adaptive wavefront control. While previous studies have clarified the formation mechanism and spherical aberration of the NAML, the behavior of off-axis coma has not yet been fully investigated. In this work, we derive the complete third-order coma expression of the NAML by combining the nonlinear refractive-index distribution with the Seidel aberration formulation. The dependence of coma on the average laser power, nonlinear-layer thickness, and incident ray angle is examined through numerical simulations. The results show that the aspheric coma component dominates and scales strongly with , leading to substantial wavefront distortion at large power, thickness, or field angle. A practical operating window is identified in which the coma remains within a few wavelengths. These findings establish the NAML as a power-tunable micro-optical element capable of partial off-axis aberration control.